Environmental entrepreneurs facilitating change toward sustainability: a case study of the wine industry in New Zealand. Issue 1 (2nd January 2016) - Zahraie, Babak; Everett, André M.; Walton, Sara; Kirkwood, Jodyanne
Abstract : This research explores the roles and strategies of environmental entrepreneurs in fostering wider change within their sociotechnical system, employing a qualitative case study in the context of the New Zealand wine industry to provide illustrative depth. A combination of strategic niche management and evolutionary theory of organizational change is used to explain the findings, focusing on the three key aspects of learning, networking, and articulation taking place at niche level. The research proposes that while environmental entrepreneurs facilitate processes of change through their actions, they are strongly influenced by broader business environment factors such as financial pressures and acceptance of their philosophies among the wider population; as a consequence, their actions indicate role shifts between being proactive, influential actors and reactive, self-centered players.